Review on ethnomedicinal claims and pharmacological activity of Asvashakhotah (Glycosmispentaphylla [Retz.] A. DC): An extrapharmacopoeial plant of ayurveda - Brijen Ramavat; Tarun Sharma; Vidhi Bapna; Payal Purohit (Wolters Kluwer Medknow Publications, 2024)
Objective: Glycosmis pentaphylla (Retz.) A. DC, family Rutaceae, unarmed shrub, known as Asvashakhotah, available in India, has numerous ethnomedical therapeutic claims and is used by many tribes to combat various disease conditions, but these claims are not documented in a single source. Thus, we have made an attempt to compile the available data in a systematic way. Data Source: The data have been compiled from available survey articles related to ethnomedicinal claims, various textbooks related to medicinal plant and research papers related to pharmacological actions. Review Methods: A concerted effort has been undertaken to compile all information from the 117 research articles and 8 books that have been published to conduct the current review. Result and Conclusion: It has been found that nearly 37 tribes in and around India employ the entire G. pentaphylla plant or its various useful parts (leaves, roots, seeds, fruits, and stems) to treat 40 different diseases. The majority of these are recommended for use both internally and externally in the treatment of fever, anemia, jaundice, rheumatism, asthma, eczema, and other conditions. A wide range of pharmacological effects was revealed by G. pentaphylla Retz., including anti-hepatocellular carcinoma, hepatoprotective, antibacterial, antifungal, anthelminthic, antioxidant, antipyretic, anti-tumor, wound healing, anti-inflammatory, insecticidal, and larvicidal activities. With the easy availability of G. pentaphylla Retz. and first-hand knowledge of its potential ethnomedicinal uses, fresh research on this plant may be initiated.